Energy Performance Indicator of a Gold Mining Industry in Indonesia - Mahandari, Cokorda Prapti; Yamin, Mohamad; Palaloi, Sudirman; Hasan, Muhammad Syukri; Kurniawan, Cucuk (Master Program in Mechanical Engineering, Gunadarma University, 2024)
Energy Audit follows ISO 50002 standard had been done on one of gold mining industry in North Maluku, Indonesia that has operations involving two underground mining. As part of the energy audit report, this paper present energy sources and energy consumption, specific energy consumption cum energy intensity of the plant. Energy audit methods include energy audit planning, opening meeting, data collection, measurement plant, siti visit, data analysis, energy audit reporting and closing audit. Most electricity data were collected from the SCADA system which the company use to monitor and control maximum electricity demand. Arithmetic mean, energy intensity equation and visual graphic methods had been employed to investigate energy profile and energy performance indicator of this gold mining. As the site located far away from the national grid then four Diesel powerhouses generates the electricity. Fuel consumption for four unit mainly electricity generation, transportation, heavy duty and supporting are investigated thoroughly. Since Diesel powerhouse occupy more than 80 % fuel consumption then the Diesel power houses is the Significant energy users (SEU). Further study SEC and on heat rate of the powerhouse is carried out and benchmarked with the IEA. It shows that the powerhouses have excellent performance as SEC and heat rate is lower than typical powerhouses. The powerhouse distributed electricity to four different unit, Kencana Underground Mining, Toguraci underground mining, Mill and Merril Crowe Processes and Supporting Unit. Among these units, Togurachi under gound mining with its uniqueness become the highest electricity end user as expected. It covers more than 40 % electricity consumption resulting quite high total energy intensity by ore milled which is approximately 475 kWh/ton (1710 MJ/ton) and energy intensity by Dore bullion is 1,420 kWh/ounce (5108 MJ/oz).